The Effectiveness of Using Mind Mapping in English Vocabulary Learning for Eleventh Grade Students at MA Darul Ihsan Samarinda - Almaidah Rahmadini Darsono; Shafa Shafa; Anis Komariah (El-Syaker : Samarinda International Journal of Language Studies, 2025)
Mind mapping is an innovative learning strategy that emphasizes creativity and visual organization to enhance comprehension and retention. However, its effectiveness in improving vocabulary acquisition, particularly in a high school setting, requires further exploration. This study investigated the application of mind mapping in fostering English vocabulary acquisition among eleventh grade students at MA Darul Ihsan Samarinda. Using a quasi-experimental design, this quantitative study involved 43 students divided into experimental and control groups. Data were collected through a pre-test and a post-test consisting of 25 multiple-choice questions. Statistical analysis, including the Mann-Whitney U test, revealed that the experimental group, taught using mind mapping, experienced a significant increase in mean score of 35.3 points, compared to 27.1 points in the control group. The findings underscore the potential of mind mapping to not only enhance vocabulary acquisition but also promote student engagement and creativity. This study advocates for the integration of mind mapping into English language teaching as an effective and practical pedagogical tool.